Breaking Dormancy of Tamarindus indica Seeds Using Diverse Mechanisms - H. Aliyu, Amina; Fatima Mato, Auwal; Abdullahi , Nafi’atu; Mohammed, Sulaiman (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Many Savannah tree species had dormant seeds and their germination is important for the plant growth and development. To achieve easy germination, this study determined the effect of seed dormancy and its breakage in Tamarindus indica (Tamarind) using diverse treatments for the seed domancy breakage. Fifty (50) seeds of Tamarind were subjected to four different treatments including mechanical abrasive, soaking in 50% concentrated sulphuric acid (H2SO4), soaking in cold and hot water, then control. The seeds were planted in polythene bags containing same type and amount of soil for germination and growth performance analysis. The seeds were allowed to grow for 8 weeks period. Mechanical scratchy gave the optimum germination performance at 100%, followed by seeds treated with hot water (80%) and the least germination performance was observed in the control. Whereas, no germination was observed from the seeds treated with sulphuric acid. Seedlings germinated from mechanical mechanism of seed dormancy breakage continue to give the best growth performance based on number of leafs per seedling, plant height and stem girth at interval of 2 weeks observation. Germination was observed to be enhanced by the effect of mechanical method on disrupting the seed coats of Tamarind. The statistically analysis at 5% significance level indicated that each treatments has significant effect on germination and growth performance of Tamarind seed. This would serve as basic information in the regeneration and improvement of Tamarind tree, as well as other native tree species that are of economic values.